MicroRNA-370 functions as a tumor suppressor in hepatocellular carcinoma via inhibition of the MAPK/JNK signaling pathway by targeting BEX2 - Wang, Xin; Zhu, Wenyan; Xu, Chuanshen; Wang, Feng; Zhu, Xiaodan; Sun, Yandong; Guo, Yuan; Fu, Xiaoyue; Zhang, Yong; Zang, Yunjin (Journal of human genetics, 2019)
Hepatocellular carcinoma (HCC) is a primary malignancy of the liver and occurs predominantly in patients with underlying chronic liver disease and cirrhosis. Accumulating studies have revealed that microRNAs (miRNAs) play a critical role in the development and progression of HCC. Through microarray-based gene expression profiling of HCC, miR-370, and BEX2 were identified in HCC. Hence, this study aimed to evaluate their abilities on the cellular processes in HCC. It was determined that BEX2 was highly expressed and miR-370 was poorly expressed in HCC cell lines and tissues. Then, the cell line presenting with the highest BEX2 expression and the lowest miR-370 expression was selected for subsequent gain- and loss-of-function experimentation. The antitumor effect of miR-370 on HCC cell proliferation, invasion, migration, and apoptosis, as well as the MAPK/JNK signaling pathway was examined. Meanwhile, the interaction among miR-370, BEX2, and MAPK/JNK signaling pathway was identified. BEX2 is verified to be a target of miR-370. Moreover, miR-370 exerted antitumor effect on HCC development through suppression of the MAPK/JNK signaling pathway by targeting BEX2. Later, it was further verified by in vivo experiment that overexpression of miR-370 inhibited tumor growth. Above results provide evidence that miR-370 could downregulate BEX2 gene and inhibit activation of MAPK/JNK signaling pathway, thus inhibiting the development of HCC. It provides a worth-trying novel therapeutic target for HCC treatment.